1995
DOI: 10.1159/000126813
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Growth Hormone-Deficient Adults with Recombinant Human Growth Hormone Increases the Concentration of Growth Hormone in the Cerebrospinal Fluid and Affects Neurotransmitters

Abstract: In a double-blind, placebo-controlled trial, the effects of recombinant human growth hormone were studied on cerebrospinal fluid concentrations of growth hormone, insulin-like growth factor 1 (IGF-1), insulin-like growth factor binding protein-3 (IGFBP-3), monoamine metabolites, neuropeptides and endogenous opioid peptides. Twenty patients, 10 patients in each of 2 groups, with adult-onset, growth hormone deficiency were treated for 1 month with recombinant human growth hormone (0.25 U/kg/week) or placebo. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(114 citation statements)
references
References 26 publications
5
107
2
Order By: Relevance
“…These GH-induced modulations in neurotransmitter levels may be responsible for the positive effect of GH on mood, since similar changes are observed following successful treatment with anti-depressives (Risby et al 1987. Increased beta-endorphin levels have also been observed in the CSF of GH-treated patients in some (Johansson et al 1995) but not all studies. Beta-endorphins are produced in regions containing GH-binding activity (pituitary and hypothalamus) and are involved in exercise-induced changes in mood (Goldfarb & Jamurtas 1997).…”
Section: Therapeutic Mechanisms: Neural Effectsmentioning
confidence: 81%
See 1 more Smart Citation
“…These GH-induced modulations in neurotransmitter levels may be responsible for the positive effect of GH on mood, since similar changes are observed following successful treatment with anti-depressives (Risby et al 1987. Increased beta-endorphin levels have also been observed in the CSF of GH-treated patients in some (Johansson et al 1995) but not all studies. Beta-endorphins are produced in regions containing GH-binding activity (pituitary and hypothalamus) and are involved in exercise-induced changes in mood (Goldfarb & Jamurtas 1997).…”
Section: Therapeutic Mechanisms: Neural Effectsmentioning
confidence: 81%
“…Long-term GH replacement in GHD men decreases dopamine turnover, as indicated by reduced CSF concentrations of homovanilic acid (a dopamine metabolite) (Johansson et al 1995. The concomitant increase in CSF aspartate concentrations and N-methyl- aspartate (NMDA) receptor activation implicates excitatory amino acids in this reduced dopamine release .…”
Section: Therapeutic Mechanisms: Neural Effectsmentioning
confidence: 99%
“…injections of GH (12,13). In one of these studies a dose-dependent increase in cerebrospinal fluid GH concentrations was confirmed (13).…”
mentioning
confidence: 78%
“…Other scientific approaches to this question provide supportive evidence that GH has direct effects on the CNS, affecting sleep patterns and the CSF concentrations of various neurotransmitters. The atypical nature of the depression, and the observation that GHD and its treatment does not alter CSF levels of 5HT or NE metabolites (3,4), suggests that these symptoms may not be readily amenable to conventional antidepressant medication. The results of our study suggest that patients with GH deficiency and impaired QOL and/or atypical depression should be given a trial of GH therapy, and that the effects of treatment can be gauged after only a few months.…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone treatment of GHDAs reduces the cerebrospinal fluid (CSF) concentrations of vasoactive intestinal peptide and of the dopamine metabolite, homovanillic acid (3,4), and may increase the CSF concentration of beta-endorphin (4) (although some researchers have found no effect (3)). However, GHD does not seem to alter the CSF levels of 5-hydroxytryptophan (5HT) or norepinephrine (NE) metabolites (3,4), which are usually thought to be the most significant monoamines in depression. Blunting of the GH response to provocation tests has been reported as a feature of major depression in non-GH deficient patients (5 -7).…”
Section: Introductionmentioning
confidence: 99%